Зародження модернізму в сакральній архітектурі - Гнатюк, Лілія Романівна (Теорія та практика дизайну, 2021)
Проаналізовано знакові храми ХХ ст. – храми Мозера в Базелі та Мецгера в Люцерні, які згадуються разом як приклади модерністської сакральної архітектури в Швейцарії. Представлено антропософську теорію архітектури, яка припускала що світ і людина пронизані різними типами духовних сил, які завдяки формам об’єктів видимого світу можуть бути зміцнені або послаблені. Репрезентовано розуміння гармонії форм у формотворенні сакрального простору. Розглянуто архітектуру сакральних споруд, зведених за принципом класицистичної архітектури. Визначено, що форми, створені Мозером та Мецгером, не належать до жодної із «мов» архітектурного виразу, які були створені дотепер. Представлено погляд на таємничу природу з’єднання людей у суспільстві – близький до видів зв’язків, що пов’язують релігійні громади, а також концепція архітектури як мосту між небом і землею, яка також змінила підхід до будівлі як виключно матеріального об’єкта. Проаналізована форми сакральної споруди та способу організації інтер’єрів, що дозволило зробити висновок, що ідеї відродження єдності навколишнього ландшафту, схильність використовувати місцеві матеріали (насамперед камінь), але також більш загальне, філософське ставлення, що дозволяє розглядати архітектуру як елемент, який пов’язує сили космосу з життям людини, що поєднує вірян різних конфесій. Розглянуто використання метафоричної мови архітектури засноване на світі візуальних людських виробів та їх іконографічних відмінних рисах. Виявлено необхідність враховувати взаємозв’язок між певними формами та повідомленнями, що через них передаються у формотворенні сакрального простору. Також представлено спробу адаптувати принципи модернізму до потреб формотворення сакрального простору. Виявлено тенденції формотворення сакрального простору у ХХ ст. Significant temples of the XX century are analyzed. — the temples of Moser in Basel and Metzger in Lucerne, which are collectively referred to as examples of modernist sacred architecture in Switzerland. An anthroposophical theory of architecture is presented, which assumed that the world and man are permeated with different types of spiritual forces, which, thanks to the forms of objects of the visible world, can be strengthened or weakened. The understanding of the harmony of forms in the formation of the sacred space is presented. The architecture of sacral buildings erected according to the principle of classical architecture is considered. It is determined that the forms created by Moser and Metzger do not belong to any of the languages ​​of architectural expression that have been created so far. The article presents a view of the mysterious nature of the connection of people in society - close to the types of connections that connect religious communities, as well as the concept of architecture as a bridge between heaven and earth, which also changed the approach to a building as an exclusively material object. The forms of sacred buildings and the way of organizing interiors were analyzed, which made it possible to conclude that the ideas of reviving the unity of the surrounding landscape, the tendency to use local materials (first of all, stone), but also a more general, philosophical attitude, which allows us to consider architecture as an element, connects the forces of space with human life uniting believers of different confessions. The article considers the use of the metaphorical language of architecture based on visual human products and their iconographic distinctive features. Revealed the need to take into account the relationship between certain forms and messages through which they are transmitted in the formation of the sacred space. An attempt is also presented to adapt the principles of modernism to the needs of the shaping of the sacred space. The tendencies of the formation of the sacred space in the XX century are revealed.